Students' Guide to Business Computing - Stang, Norman; Blewett, Frank (Newnes, 2014)
Students' Guide to Business Computing discusses topics concerning the use of computers in business. The book is comprised of nine chapters that define systems requirements and discuss the issues in designing a system. Chapter 1 covers the business enterprise, while Chapter 2 tackles business computers. Chapter 3 talks about initiating the systems development life cycle, and then Chapter 4 deals with determining system requirements. The book also covers systems design and choosing and using a programming language. Applications software and systems testing and implementation are also discussed. The last chapter talks about selecting business computing hardware and software. The text will be useful to entrepreneurs who want to integrate information technology into their business.